2016
DOI: 10.1111/1745-9125.12123
|View full text |Cite
|
Sign up to set email alerts
|

Risk, Race, and Recidivism: Predictive Bias and Disparate Impact*

Abstract: One way to unwind mass incarceration without compromising public safety is to use risk assessment instruments in sentencing and corrections. Although these instruments figure prominently in current reforms, critics argue that benefits in crime control will be offset by an adverse effect on racial minorities. Based on a sample of 34,794 federal offenders, we examine the relationships among race, risk assessment [the Post Conviction Risk Assessment (PCRA)], and future arrest. First, application of well‐establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(124 citation statements)
references
References 60 publications
4
117
3
Order By: Relevance
“…Although some researchers have found that race and risk interaction is not a major concern and risk assessments have the potential to be race neutral (Skeem and Lowenkamp, ), it is more important to understand mechanisms that perpetuate racial biases in lieu of risk assessment and how these factors may explain the findings in this study. Understanding the nature of risk assessment and how well they perform relies on the ability to understand how these tools are implemented in practice and the factors that may moderate their predictive validity.…”
Section: Discussionmentioning
confidence: 92%
“…Although some researchers have found that race and risk interaction is not a major concern and risk assessments have the potential to be race neutral (Skeem and Lowenkamp, ), it is more important to understand mechanisms that perpetuate racial biases in lieu of risk assessment and how these factors may explain the findings in this study. Understanding the nature of risk assessment and how well they perform relies on the ability to understand how these tools are implemented in practice and the factors that may moderate their predictive validity.…”
Section: Discussionmentioning
confidence: 92%
“…To determine this, we would need to be able to compare the accuracy of more specific and less specific tools using relevant, reliable and unbiased data on accuracy. Currently deployed tools frequently do use demographic factors such as age and immigration status as predictors, and although recent evidence suggests that including such demographic factors improves predictive accuracy [34], [35], further data are needed to confirm this.…”
Section: Discrimination and Stigmatisationmentioning
confidence: 99%
“…While third‐generation risk instruments can be and often are linked with rehabilitative programming, research on contemporary risk‐based reform is incipient; at this point, there is almost no evidence on how risk instruments effect either incarceration rates or crime rates (Stevenson, ) . And numerous questions remain about the validity, implementation, ethics, and even constitutionality of risk instruments (Berk, Heidari, Jabbari, Kearns, & Roth, ; Cheliotis, ; Desmarais et al, ; Hannah‐Moffat, ; Harcourt, ; Kemshall, ; Klingele, ; Rothschild‐Elyassi et al, ; Skeem & Lowenkamp, ; Starr, ; Taxman & Caudy, ).…”
Section: Risk‐based Reform?: Promises and Perilsmentioning
confidence: 99%